2013
DOI: 10.1371/journal.pone.0077411
|View full text |Cite
|
Sign up to set email alerts
|

Minnelide: A Novel Therapeutic That Promotes Apoptosis in Non-Small Cell Lung Carcinoma In Vivo

Abstract: BackgroundMinnelide, a pro-drug of triptolide, has recently emerged as a potent anticancer agent. The precise mechanisms of its cytotoxic effects remain unclear.MethodsCell viability was studied using CCK8 assay. Cell proliferation was measured real-time on cultured cells using Electric Cell Substrate Impedence Sensing (ECIS). Apoptosis was assayed by Caspase activity on cultured lung cancer cells and TUNEL staining on tissue sections. Expression of pro-survival and anti-apoptotic genes (HSP70, BIRC5, BIRC4, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 87 publications
2
52
0
Order By: Relevance
“…Previous studies have shown that Minnelide, a water soluble analog of triptolide, is effective in pancreatic, gastric and osteosarcoma [9,10,3, 5,13]. We have found that Minnelide is an active agent against ovarian cancer both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Previous studies have shown that Minnelide, a water soluble analog of triptolide, is effective in pancreatic, gastric and osteosarcoma [9,10,3, 5,13]. We have found that Minnelide is an active agent against ovarian cancer both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 76%
“…Others have shown that Minnelide exhibits anti-proliferative effects in non-small cell lung cancer by promoting apoptosis in vitro and in vivo [10]. Further, Minnelide has been shown to reduce tumor burden and metastasis in an orthotopic model of osteosarcoma [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triptolide induces cell death in pancreatic cancer cells and markedly reduces the growth and loco-regional spread of pancreatic tumors in animal models (4). We have also shown that triptolide is effective against osteosarcoma (5), lung cancer (6), cholangiocarcinoma (7) and neuroblastoma (8). Others have shown that triptolide is effective against melanoma (9), gastric (9), breast (9) and colon cancer (10, 11).…”
mentioning
confidence: 94%
“…Inhibition of this pathway may prove clinically effective in decreasing metastatic spread. Minnelide™, a pro-drug derived from triptolide, has been shown in several cancers to downregulate NF-κB activity 17-19 .…”
Section: Introductionmentioning
confidence: 99%